The Effect Of Giving Ginger Drink On Emesis Gravidarum In 1st Trimester Pregnant Women At The Gedung Karya Jitu Health Center - rika agustina; Diana Fitri; Elsy Juni; Riona Sanjaya (POLTEKKES KEMENKES YOGYAKARTA, 2025)
The prevalence of emesis gravidarum in pregnant women in Indonesia is 14.8%. Based on the Lampung Province Health Profile, incidence of emesis gravidarum in pregnant women is 50-90%. This study aims to determine the effect of giving ginger drink on emesis gravidarum in first trimester pregnant women. Type of quantitative research and pre-experimental plan with one group pre test-post test design. The subjects of this research were all 20 pregnant women in the first trimester, using a purposive sampling technique. Data analysis test used in dependent t research (paired t test). The results of the study showed that the average emesis gravidarum in first trimester pregnant women before being given ginger drink had an average value of 9.65 and a standard deviation of 1.309. The average emesis gravidarum in first trimester pregnant women after being given ginger drink had an average value of 4.60 and a standard deviation of 0.940. There is an effect of giving ginger drink on emesis gravidarum in first trimester pregnant women, with p-value = 0.000. It is recommended that pregnant women carry out routine pregnancy checks and carry out ginger drink therapy at home to reduce nausea and vomiting in the first trimester of pregnancy